A Small Molecule that Induces Intrinsic Pathway Apoptosis with Unparalleled Speed - Palchaudhuri, Rahul (Cell Rep, 2015)
Apoptosis is generally believed to be a process that requires several hours, in contrast to non-programmed forms of cell death that can occur in minutes. Our findings challenge the time-consuming nature of apoptosis as we describe the discovery and characterization of a small molecule, named Raptinal, which initiates intrinsic pathway caspase-dependent apoptosis within minutes in multiple cell lines. Comparison to a mechanistically diverse panel of apoptotic stimuli reveals Raptinal-induced apoptosis proceeds with unparalleled speed. The rapid phenotype enabled identification of the critical roles of mitochondrial voltage-dependent anion channel function, mitochondrial membrane potential/coupled respiration, and mitochondrial complex I, III and IV function for apoptosis induction. Use of Raptinal in whole organisms demonstrates its utility to study apoptosis in vivo for a variety of applications. Overall, rapid inducers of apoptosis are powerful tools that will be used in a variety of settings to generate further insight into the apoptotic machinery.